2020
DOI: 10.1038/s41416-020-0797-7
|View full text |Cite
|
Sign up to set email alerts
|

The prognostic significance of immune microenvironment in breast ductal carcinoma in situ

Abstract: Background The role of different subtypes of tumour infiltrating lymphocytes (TILs) in breast ductal carcinoma in situ (DCIS) is still poorly defined. This study aimed to assess the prognostic significance of B and T lymphocytes and immune checkpoint proteins expression in DCIS. Methods A well characterised DCIS cohort ( n = 700) with long-term follow-up comprising pure DCIS ( n = 508) and DCIS mixed with invasive ca… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
33
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 36 publications
(37 citation statements)
references
References 71 publications
4
33
0
Order By: Relevance
“…Different stromal lymphocyte composition between DCIS and IBC may be another answer for the potential different roles in their prognostic significance and relation with the underlying genomic instability. 35 Immunofluorescence analysis showed more activated CD8 + T cells in DCIS than in IBC whereas T cells of IBC samples were more similar to Tregs, suggesting a stronger immunosuppression in IBC compared with DCIS. 10 Modern immune researches have focused on the characteristics of different subtypes of TILs in DCIS and their relation with recurrence risk.…”
Section: Discussionmentioning
confidence: 90%
“…Different stromal lymphocyte composition between DCIS and IBC may be another answer for the potential different roles in their prognostic significance and relation with the underlying genomic instability. 35 Immunofluorescence analysis showed more activated CD8 + T cells in DCIS than in IBC whereas T cells of IBC samples were more similar to Tregs, suggesting a stronger immunosuppression in IBC compared with DCIS. 10 Modern immune researches have focused on the characteristics of different subtypes of TILs in DCIS and their relation with recurrence risk.…”
Section: Discussionmentioning
confidence: 90%
“…15,16,[23][24][25][26] Toss et al characterised immune subtypes in 508 patients with pure DCIS and although they found that high expression levels of the immunosuppressive proteins stromal FOXP3 and PD-L1 were poor prognostic factors for recurrence, in multivariate analysis overall touching TIL density was the strongest independent predictor of DCIS recurrence. 27 They concluded that assessment of TILs on H&E-stained slides could provide the greatest prognostic data without the need for immune marker assessment. 27 In our study, patients with DCIS showing high nuclear grade and/or necrosis were significantly less likely to have a low ODX DCIS Score.…”
Section: Discussionmentioning
confidence: 99%
“…27 They concluded that assessment of TILs on H&E-stained slides could provide the greatest prognostic data without the need for immune marker assessment. 27 In our study, patients with DCIS showing high nuclear grade and/or necrosis were significantly less likely to have a low ODX DCIS Score. Furthermore, stromal TILs and touching TILs were associated with high nuclear grade, but circumferential TILs were not.…”
Section: Discussionmentioning
confidence: 99%
“…Evaluation of IES for the prognostic prediction of HER2-positive BC in TCGA cohort and METABRIC cohort From a variety of studies, it is now well established that immune functions play an important prognostic role in BC [21][22][23] . Thus, we sought to explore whether the IES as a predictor in HER2-positive BC has prognostic potential.…”
Section: Ies Is Associated With Fgfr1 Signaling In Her2-positive Bcmentioning
confidence: 99%